‏ Digital transformation and its role in achieving social security: Field study in the Iraqi National Security Service - SAHI, SAIF; Qanbar, Firas (Al-Adab Journal, 2024)
This study, titled (Digital Transformation and its Role in Achieving Social Security), sought to identify digital transformation, the foundations of its establishment and stages, as well as its advantages and disadvantages, Also, identifying the dimensions of social security, its threats, means of achieving it, and the effective factors in it. As well as knowing the role of digital transformation in combating administrative corruption, the descriptive and analytical approach was adopted on a purposive sample of (250) respondents from three departments in the Iraqi National Security Service, the questionnaire was used as a means of collecting data The study reached several results, the most important of which is that digital transformation has contributed to raising the performance of security institutions, that digital transformation processes are well accepted in society, and that investing in digital transformation has contributed primarily to (reducing the spread of administrative and financial corruption), in addition to that digital transformation Its methods have contributed to achieving social security and social justice